The Acceptability and Appropriateness of a Collaborative, Sport-Centered Mental Health Service Delivery Model for Competitive, and High-Performance Athletes - Van Slingerland, Krista J.; Durand-Bush, Natalie (Frontiers in Sports and Active Living, 2021)
The purpose of this study was to evaluate the acceptability and appropriateness of a sport-centered, collaborative mental health service delivery model implemented within the Canadian Centre for Mental Health and Sport (CCMHS) over a period of 16 months. The study is situated within a larger Participatory Action Research (PAR) project to design, implement and evaluate the CCMHS. Primary data were collected from CCMHS practitioners (n = 10) and service-users (n = 6) through semi-structured interviews, as well as from CCMHS stakeholders (n = 13) during a project meeting, captured via meeting minutes. Secondary data derived from documents (e.g., clinical, policy, procedural; n = 48) created by the CCMHS team (i.e., practitioners, stakeholders, board of directors) during the Implementation Phase of the project were reviewed and analyzed to triangulate the primary data. The Framework Method (Ritchie and Spencer, 1994) was used to organize, integrate and interpret the dataset. Overall, results indicate that both practitioners and service-users found the model to be both acceptable and appropriate. In particular, practitioners’ knowledge and experience working in sport, a robust intake process carried out by a centralized Care Coordinator, and the ease and flexibility afforded by virtual care delivery significantly contributed to positive perceptions of the model. Some challenges associated with interprofessional collaboration and mental health care costs were highlighted and perceived as potentially hindering the model’s acceptability and appropriateness.